Enhancement of Metal-Metal Coupling at a Considerable Distance by Using 4-Pyridinealdazine as a Bridging Ligand in Polynuclear Complexes of Rhenium and Ruthenium - Cattaneo, Mauricio (2006)
Novel polynuclear complexes of rhenium and ruthenium containing PCA (PCA = 4-pyridinecarboxaldehyde azine or 4-pyridinealdazine or   1,4-bis(4-pyridil)-2,3-diaza-1,3-butadiene) as a bridging ligand  have been synthesized as PF6- salts and characterized by spectroscopic, electrochemical and photophysical techniques.  The precursor mononuclear complex, of formula [Re(Me2bpy)(CO)3(PCA)]+, (Me2bpy = 4,4´-dimethyl-2,2´-bipyridine), does not emit at room temperature in CH3CN and the transient spectrum found by flash photolysis at lexc = 355 nm can be assigned to a MLCT (metal-to-ligand charge transfer) excited state [(Me2bpy)(CO)3ReII(PCA-)]+, with lmax = 460 nm and t < 10 ns. The spectral properties of the related complexes [{Re(Me2bpy)(CO)3}2(PCA)]2+,  [Re(CO)3(PCA)2Cl] and [Re(CO)3Cl]3(PCA)4 confirm the existence of this low-energy MLCT state. The dinuclear complex, of formula  [(Me2bpy)(CO)3ReI(PCA)RuII(NH3)5]3+, presents an intense  absorption in the visible spectrum that can be assigned  to a MLCT dp(Ru) ® p*(PCA); in CH3CN, the value of l max = 560 nm is intermediate between those  determined for [Ru(NH3)5(PCA)]2+ (lmax = 536 nm) and [(NH3)5Ru(PCA)Ru(NH3)5]4+ (lmax = 574 nm), indicating a significant decrease in the energy of the p*-orbital of PCA. The mixed valent species, of formula [(Me2bpy)(CO)3ReI(PCA)RuIII(NH3)5]4+, was obtained in CH3CN solution, by bromine oxidation or by controlled potential electrolysis at  0.8 V in a OTTLE cell of the [ReI,RuII] precursor ; the band at lmax = 560 nm disappears completely and a new band appears at  lmax = 483 nm , assignable to a MMCT band (metal-to-metal charge transfer) ReI ® RuIII. By using the Marcus-Hush formalism, both the electronic coupling (HAB) and the reorganization energy (l) for the metal-to-metal intramolecular electron transfer have been calculated. In spite of the considerable distance between both metal centers (~ 15.0 Å), there is a moderate coupling that, together with the comproportionation constant of the mixed-valent species [(NH3)5Ru(PCA)Ru(NH3)5]5+  (Kc ~ 102, in CH3CN), put into evidence an unusual enhancement of the metal-metal coupling in the bridged PCA complexes. This effect can be accounted for by the large extent of  ?metal-ligand interface?, as shown by DFT calculations on free PCA . Moreover,  l is lower than the driving force -DG°  for the recombination charge reaction [ReII, RuII ] ® [ReI, RuIII] that follows light excitation of the mixed valent species. It is then predicted that this reverse reaction falls in the Marcus inverted region, making the heterodinuclear [ReI,RuIII] complex a  promising model for controlling the efficiency of charge-separation processes.